I know what I'm doing, and other lies I tell myself : dispatches from a life under construction - Kirkman, Jen, 1974- (Simon & Schuster, 2016)
"Jen offers up all the gory details of a life permanently in progress. She reassures you that it's okay to not have life completely figured out, even when you reach middle age (and find your first gray pubic hair). She talks about making unusual or unpopular life decisions (such as cultivating a 'friend with benefits' or not going home for the holidays) because you don't necessarily want for yourself what everyone else seems to think you should. It's about renting when everyone says you should own, dating around when everyone thinks you should settle down, and traveling alone when everyone pities you for going to Paris without a man"--Amazon.com.